Comparative MRI compatibility of 316L stainless steel alloy and nickel-titanium alloy stents - Holton, Andrea D.; Walsh, Edward G.; Anayiotos, Andreas (My University, 2002)
The initial success of coronary stenting is leading to a proliferation in peripheral stenting. A significant portion of the stents used in a clinical setting are made of 316 low carbon stainless steel (SS). Other alloys that have been used for stent manufacture include tantalum, MP35N, and nickel-titanium (NiTi). The ferromagnetic properties of SS cause the production of artifacts in magnetic resonance imaging (MRI). The NiTi alloys, in addition to being known for their shape memory or superelastic properties, have been shown to exhibit reduced interference in MRI. Thus, the objective of this study was to determine the comparative MRI compatibility of SS and NiTi stents. Both gradient echo and spinecho images were obtained at 1.5 and 4.1 T field strengths. The imaging of stents of identical geometry but differing compositions permitted the quantification of artifacts produced due to device composition by normalizing the radio frequency shielding effects. These images were analyzed for magnitude and spatial extent of signal loss within the lumen and outside the stent. B 1 mapping was used to quantify the attenuation throughout the image. The SS stent caused significant signal loss and did not allow for visibility of the lumen. However, the NiTi stent caused only minor artifacting and even allowed for visualization of the signal from within the lumen. In addition, adjustments to the flip angle of standard imaging protocols were shown to improve the quality of signal from within the lumen.
Keywords: Magnetic resonance imaging.; Titanium; Stainless steel